2011
DOI: 10.1002/hep.24441
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs-372/373 promote the expression of hepatitis B virus through the targeting of nuclear factor I/B

Abstract: MicroRNAs (miRNAs) play important roles in the posttranscriptional regulation of gene expression. Recent evidence has indicated the pathological relevance of miRNA dysregulation in hepatitis virus infection; however, the roles of microRNAs in the regulation of hepatitis B virus (HBV) expression are still largely unknown. In this study we identified that miR-373 was up-regulated in HBV-infected liver tissues and that the members of the miRs-371-372-373 (miRs-371-3) gene cluster were also significantly co-up-reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
81
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(83 citation statements)
references
References 36 publications
2
81
0
Order By: Relevance
“…Interestingly, miR-373 upregulation does not correlate with HCV load in patient sera. miR-373 was upregulated in HBV-infected liver tissues, and miR-373 expression promotes HBV expression by involving the NFIB transcription factor (32), although modulation of the JAK/STAT signaling pathway was not studied. Since miR-373 expression is upregulated in chronic HCV infection and modulates the innate immune system, it will be important to investigate the status of miR-373 in other chronic infections.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, miR-373 upregulation does not correlate with HCV load in patient sera. miR-373 was upregulated in HBV-infected liver tissues, and miR-373 expression promotes HBV expression by involving the NFIB transcription factor (32), although modulation of the JAK/STAT signaling pathway was not studied. Since miR-373 expression is upregulated in chronic HCV infection and modulates the innate immune system, it will be important to investigate the status of miR-373 in other chronic infections.…”
Section: Discussionmentioning
confidence: 99%
“…Despite inhibition of HBV infection by miRNA machinery, some miRNAs appear to have positive effects on HBV replication. The miR-372/373 promotes HBV expression by targeting the nuclear factor I/B (16), and miR-1 enhances HBV replication by targeting the host gene histone deacetylase 4 (17). Considerable progress has been made in the understanding of miRNAs and HBV replication, but the complex regulatory networks involving miRNAs have not been evaluated comprehensively in HBV replication.…”
Section: Hepatitis B Virus (Hbv)mentioning
confidence: 99%
“…*, P Ͻ 0.05; **, P Ͻ 0.01; ***, P Ͻ 0.001. and PRRSV titers (data not shown), which indicated that NFIA, NFIB, IRAK1, IRAK4, IRF1, IRF9, IFNAR1, and IFNAR2 are involved in PRRSV replication regulated by miR-373. Previous studies have shown that NFIB (35) and IRF9 (36) were the target genes of miR-373, so NFIA, NFIB, IRAK1, IRAK4, IRF1, and IRF9 were selected to confirm that the potential target genes described above were also the target genes of miR-373.…”
mentioning
confidence: 99%